Concurrence of de-alloying and re-alloying in a ternary Al67Cu18Sn15 alloy and the fabrication of 3D nanoporous Cu–Sn composite structures. Issue 13 (14th February 2015) - Song, T.; Yan, M.; Gao, Y.; Atrens, A.; Qian, M.
<x xml:space="preserve">Abstract</x> The creation of nanoporous Cu3Sn–Cu–Cu6Sn5 composite structures in the form of self-supporting foils through the concurrence of de-alloying and re-alloying.